How Alphabet Knowledge Impacts Reading Development - Nicole Hertz (The Advocate, 2024)
In this article, the relationship between alphabet knowledge and reading development will be explored. Key topics will include how alphabet knowledge is not only a predictor for future reading success, but also how letters and their sounds serve as a bridge from a pre-alphabetic phase into a partial alphabetic phase, and beyond. Since each phase is characterized by students’ understanding of the alphabet system, which is central to word reading skill, movement within the phases helps support reading proficiency. Knowledge of these phases can support pre-service teachers and school leaders with instruction, assessment, differentiation, and intervention. Other instructional considerations will also be examined.